2019
DOI: 10.1007/s12253-019-00788-w
|View full text |Cite
|
Sign up to set email alerts
|

KIT Mutation Incidence and Pattern of Melanoma in Central Europe

Abstract: Data on the KIT mutation rate in melanoma in the central European region is missing. Accordingly, in a cohort of 79 BRAF/ NRAS double wild type cutaneous melanoma and 17 mucosal melanoma KIT mutation was assessed by Sanger sequencing of exons 9,11,13,17 and 18. In this cutaneous melanoma cohort KIT mutation frequency was found to be 34/79 (43.04%) with a significantly higher rate in acrolentiginous melanoma (ALM) as compared to UV-induced common variants (20/34, 58.8% versus 14/45, 31.1%, p = 0.014). In the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Inhibiting the expression of KIT could improve the prognosis of patients with cancer [ 41 , 42 ]. Studies have shown that in patients with melanoma, KIT variants could be classified as a rare subtype [ 43 , 44 ]. VWF is also important in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the expression of KIT could improve the prognosis of patients with cancer [ 41 , 42 ]. Studies have shown that in patients with melanoma, KIT variants could be classified as a rare subtype [ 43 , 44 ]. VWF is also important in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…KIT (C-KIT/CD117) gene mutations show heterogeneous distribution through the gene and they have been detected in hot-spots at exon 9 (c459/465/ 471/483), 11 (c551/559/576), 13 (c642), and 17 (c816), accounting for 5-15% of mutations of diagnosed melanomas. In light of the relatively high mutation rate of KIT in cutaneous melanoma and since BRAF, KIT, and NRAS mutations appear to be mutually exclusive, the screening of KIT mutations, at least in exons 9/11/13, is suggested in BRAF/NRAS double-wild-type melanoma patients (31,34,45,46).…”
Section: Current Knowledge Of Genetic Alterations In Cutaneous Melanomamentioning
confidence: 99%
“…Activating mutations in c-KIT are identified in approximately 15.6% of mucosal melanomas and 23% of acral melanomas and these numbers rises up to 39% and 36% respectively when KIT copy number increases [ 129 , 130 ]. c-KIT mutations are most commonly found in exons 9 and 11 [ 131 ]. Mutations in c-KIT can either activate or deactivate the receptor, causing varying downstream functional consequences in different cancers.…”
Section: C-kitmentioning
confidence: 99%